Alkaline activation of clayey soil using Potassium hydroxide & Fly ash - Elkhebu, Ahmed Giuma; Zainorabidin, Adnan; Bujang, Huat B. K; Bakar, Ismail Hj.; Abdeljouad, Lokman Abdeljouad; Dheyab, Wisam khalef (International Journal of Integrated Engineering, 2019)
In this paper the potential of introducing alkali activated fly ash to a clayey soil as stabilizing agent was investigated. As alkaline activator Potassium hydroxide of 12 M was introduced to the soil fly ash mixtures. Unconfined compressive strength tests were carried out. Four different fly ash/solid ratios were proposed to be 10 %, 20 %, 30 % and 40 % at two curing regimes of 7 & 28 days. The greatest unconfined compressive strength was of 40 % mixture recorded at 3.68 Mpa after 28 days. Microstructural analyses including SEM, EDS and FTIR were conducted to detect and confirm gel formation. Alkaline activation of clayey soil using KOH solution as an activator proved to be a feasible alternative for soft soil stabilization.